الدفع بعدم الدستورية كآلية لحماية الحقوق والحريات في النظام القانوني الجزائري - قدة, حنان (Universty of Eloued جامعة الشهيد حمة لخضرالوادي, 2023)
الملخص: تتناول هذه الدراسة آلية الدفع بعدم الدستورية، والتي تعد من مستجدات التعديل الدستوري لسنة 2016، وتضمنها أيضا التعديل الدستوري لسنة 2020 في المادة 195 منه، إذ يكتسي هذا الموضوع أهمية بالغة، تتجلى في دو ملخص بالانجليزية Abstract: This study tackles michanism of the actions of unconstitutionality, which is considered as one of of the contitutional reform amendment of 2016, and also includes the constitutional amedment of 2020 in article 195 thereof. The subject enjoys a great deal of significance, the role of this mechanism is evident in the protection of the rights and freedoms, for it is a right to any litigant who claims a certain legislative or organisational provision is violating the rules the constitution guarantees until this provision is transmitted to the Constitutional Court to determine its constitutionality. Thus, litigants in conjunction with the judiciary power have a role to play in triggering oversight on the constitutionality of laws. Our treatment of this issue will be through the tracking of the procedure of the unconstitutional plea from its raising before the judiciary until its adjudication by the Constitutional Court. and the extent to which these controls and procedures affect constitutional rights and freedoms, exposing us to the conditions of acceptance and transmission to referrals the Supreme Court or the Conseil d'Etat, as the case may be, to be liquidated again for referral to the Constitutional Court constitutionality ", where the latter adjudicates on the constitutionality of the challenged provision by binding final decision.
أطروحة دكتوراه تخصص قانون الدولة والمؤسسات في الحقوق و العلوم السياسية
Keywords: الدفع بعدم الدستورية- الجهات القضائية –الحقوق والحريات- المحكمة الدستورية; the actions of unconstitutionality- Judicial authorities- Rights and freedoms Constitutional Court